Factors Determining the Welfare of Family Circular Mobility of Labor from Nusa Penida in the Tourism Sector in Ubud - Putu Ari Kusumadewi; Surya Dewi Rustariyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main motivation for people to move from their area (rural) to urban is an economic motive. This motive developed due to economic inequality between regions. The most recommended condition is a rational consideration, where individuals mobilize to the city is the expectation of getting a job and earning a higher income than what is obtained in the village (Mantra, 1992). The purpose of this study is to determine the Determinants of Family Welfare of Circular Mobility Actors of Labor from Nusa Penida in the Tourism Sector in Ubud. The research method used is associative because it aims to find the influence of independent variables on one or more dependent variables. The results of the study concluded that: Employment status directly has a positive and significant effect on circular migrant remittances in Ubud District. Then skills, employment status and education level directly have a positive and insignificant effect on circular migrant remittances in Ubud District. Remitan has no positive and insignificant effect on circular migrant remittances in Ubud District.